RUNTUHNYADUNIA TAKHAYUL DAN PERKEMBANGAN AGAMA DI NEGARABARATPADA AKHIR ABAD 20 - Nazar Naamy (TASÂMUH, 2017)
The development of religion in the West at the end of the 20th century in Andrew Greeley’s view has increased in some former communist countries, especially Russia. While in other countries has decreased as in England, Netherlands, and France. In some countries it is relatively unchanged, especially the traditional Catholic countries, and in some societies the social democracy has declined and there has been an increase. Whereas in the case of individuals, Greeley finds that religion becomes more important for people as they age. Greeley observed that the survey results showed a lack of interest in religion among young people and tended to ignore it. This is due to the correlation related to lifecycle issues and not a sign of social change. In connection with the disappearance of the real world of superstition in the 17th century scientists tried to eliminate the mystical and superstitious patterns of thought and provide a more scientific and experimental pattern of thought, so that in the west in the 17th century it became history and witness that the era of superstition has begun to disappear. The superstition in western tradition is not easy to destroy because it takes a long time span of about 1563-1762 years.